Muscle pain: understanding the mechanisms - Mense, Siegfried; Gerwin, Robert D. (Springer-Verlag Berlin Heidelberg, 2010)
The two books Muscle Pain: Understanding the Mechanisms and Muscle Pain: Diagnosis and Treatment will help the practitioner to understand why the patients feel pain, what to do about it and why the treatment works. In contrast to proceedings of scientific meetings on muscle pain, they center on practical aspects and can be used by the practitioner in his or her daily work. The two books together provide a unique combination of broad basic knowledge with comprehensive clinical information on the management of patients.
Includes bibliographical references and index
Keywords: Aufsatzsammlung; Pathophysiologie; Myalgie